2013
DOI: 10.1080/15685551.2013.840481
|View full text |Cite
|
Sign up to set email alerts
|

An efficient approach for the synthesis of thermoset polyurethane acrylate polymer and its film properties

Abstract: The new allyl((2-oxo-1,3-dioxolan-4-yl)methyl) carbonate (ADC) monomer was synthesized by reacting glycerol carbonate with allylchloroformate. The structure of the monomer was characterized by FT-IR, 1 H NMR, UV-visible, and mass spectroscopies. The ADC monomer was copolymerized with Methyl methacrylate and butyl Acrylate by solution polymerization technique. Further, the ADC copolymer was cross-linked with 1,3-diaminopropane which yields polyurethane acrylate copolymer. The cured film was characterized by FT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The transmittance phenomenon highly depends upon the crosslink density of the polymer. The higher transparency of the coating was ascribed to the better crosslinking of the copolymer whereas the lower crosslink density resulted in a lower degree of transparency in the PU coating 19–20 . Sun et al 21 reported that the irregularity of the polymer chain due to weak intermolecular force resulted in the formation of the amorphous state that provides better transparency to the PU coatings.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The transmittance phenomenon highly depends upon the crosslink density of the polymer. The higher transparency of the coating was ascribed to the better crosslinking of the copolymer whereas the lower crosslink density resulted in a lower degree of transparency in the PU coating 19–20 . Sun et al 21 reported that the irregularity of the polymer chain due to weak intermolecular force resulted in the formation of the amorphous state that provides better transparency to the PU coatings.…”
Section: Resultsmentioning
confidence: 99%
“…The higher transparency of the coating was ascribed to the better crosslinking of the copolymer whereas the lower crosslink density resulted in a lower degree of transparency in the PU coating. [19][20] Sun et al 21 reported that the irregularity of the polymer chain due to weak intermolecular force resulted in the formation of the amorphous state that provides better transparency to the PU coatings. Hence, as observed from the test results reported in Table 3, the coatings aePU-5 and aePU-6 at AP:EP ratio of 60:40 and 50:50 exhibited optimum performance.…”
Section: Haze and Luminous Transmittancementioning
confidence: 99%
“… a (a and c) Synthesis of glycerol-based carbonate monomers ( M1 – M3 ) using a one-pot approach. (b) Two-step literature procedures for the synthesis of the same monomers. ,,, . …”
Section: Resultsmentioning
confidence: 99%
“…Since their discovery in 1930 by Otto Bayer [1], polyurethanes (PU)s production and use keep growing interest. Various physical aspects of PU materials have been investigated including coatings [2,3], adhesives [4,5], rigid or soft foams [6][7][8] and thermosets [9]. Based on the alcohol-isocyanate reaction, a well-understanding relationship between the structure of the precursors (mainly polyether polyol or polyester polyol [10][11][12]) and the properties of the resulting materials has already been established [13,14].…”
Section: Introductionmentioning
confidence: 99%